Improving Collaboration Ability Through the Jigsaw Type Cooperative Learning Model for Early Age Children 5-6 Years at the Pembina Muara Bulian State Kindergarten, Batanghari Regency, Jambi Province - Hayati, Melija; Hakim, Lukman; Hindun (International Journal of Advanced Multidisciplinary, 2024)
This research aims to examine children's cooperative abilities using the jigsaw type cooperative learning model in early childhood at the Pembina Muara Bulian State Kindergarten, Batanghari Regency, Jambi Province. Collaboration referred to in this research is an interaction or relationship between students and teachers or between students and other students in order to achieve learning goals. This type of research is Classroom Action Research (CAR), which is a method where a group of people can organize circumstances in which they can take lessons from their own experiences and make those lessons available to others. Where the teacher is the implementer of learning while the researcher is the observer. This research design uses the Kemmis and Mc Taggart model. This research is in the odd semester 2023/2024, namely in February. The subjects of this research were students at the Pembina Muara Bulian State Kindergarten, consisting of 15 people. The object of research is students' cooperation abilities. Data collection techniques use observation, interviews, questionnaires and documentation. The data was analyzed descriptively and presented in the form of tables and graphs. The results of the research showed that there was an increase in children's cooperation through the pre-cycle with a percentage of 44.44%, an increase of 0.9% in cycle 1 to 45.37% and when carried out in cycle 2 it increased by 17.09% in cycle 2 to 62.46% and when done in cycle 3 it increases by 21.24% in cycle 3 to 83.70%. With the increase in the percentage of children's social development to achieve success of more than 80% in the very well developed category, the process of improving the cooperation of children aged 5-6 years through the jigsaw type cooperative learning model has been completed and achieved the target.